Cartographies of ambivalence: allegory and cognitive mapping in Don DeLillo's later novels. Issue 8 (14th September 2018) - Beckman, Frida
ABSTRACT: Along with questions of how our geopolitical realities have developed over past decades come questions of how to grasp the logic of a globalized world that seems to have grown both smaller and larger at the same time. Central to current discussions are the roles of cognitive mapping and allegory. Fredric Jameson's long-standing project on these matters has recently been criticized for affirming rather than challenging the all-encompassing tendencies of contemporary capitalism. Whether we agree or not, such concerns indicate that it is time to revisit Jameson's project in the light of recent political developments. This article analyses three of Don DeLillo's later novels whose recurring preoccupation with the possibility of literary writing to intervene in an increasingly all-encompassing economic and political logic serves well to interrogate further the relation between the intensification of capitalism and cognitive mapping as a literary and political strategy. Cosmopolis (2003), Falling Man (2007), and Point Omega (2010), it will be argued, offer three different ways into thinking about the challenges to projects of cognitive mapping today.